Health status of senior netball players, their medication use and attitudes towards doping - de Abreu, Micaela; Nolte, Kim; Janse van Rensburg, Dina Christa; Swart, Xan (Frontiers in Sports and Active Living, 2024)
Limited research exists on the health and injuries of South African senior netball players. Senior netball players may be at greater risk of injuries and chronic disease due to their age. To treat these conditions, they may use prescription and over-the-counter (OTC) medications and, therefore, may be more vulnerable to unintentional doping. The primary aim of this study was to determine the health status, medication use and attitudes towards doping of South African senior netball players. A cross-sectional descriptive design was employed to collect data by means of an online survey. The validated 8-item Performance Enhancement Attitudes Scale (PEAS) was used to gather information on the netball player's attitudes towards doping. Descriptive statistics were used to describe the data using proportions (categorical), means (normally distributed, continuous) and medians (non-normal distributed, continuous). Doping prevalence and accompanying 95% confidence interval were calculated. Sixty senior netball players consented and completed the self-report questionnaire. The prevalence of chronic disease was 11.67%. Asthma and other conditions such as depression and attention-deficit/hyperactivity (ADHD) had the highest prevalence of 3.33%. The prevalence of chronic prescription medication use was 8.33% and 66.67% of the netball players reported receiving prescription injections, medications or utilizing OTC medications for treating injury or illness suffered 1–6 weeks before or during competition. The netball players do not have a lenient attitude towards doping. The prescription and OTC medication use could put this cohort of netball players at risk of unintentional doping. Anti-doping education aimed at senior athletes may be beneficial to reduce the risk of unintentional doping due to prescription and OTC medication use for injury or illness.